Kedudukan Sanksi Pidana dalam Undang-Undang Nomor 2 Tahun 2014 Undang-Undang Jabatan Notaris Atas Terjadinya Pemalsuan Akta Otentik - Praja Pranoto; Isnaini Isnaini; Sri Pinem (Mahesa Research Center, 2023)
The purpose of this research is to investigate and analyse the criminal law in Indonesia regarding the falsification of authentic acts, the position of acts made before Notaris and Notaris' responsibility for acts made before it containing the elements of the criminal act of falsification. The type of research used is normative law research or doctoral law research, because this research is done or shown only on written rules or other legal materials. Hasil pembahsan menyatakan bahwa Dibentuknya kejahatan pemalsuan ini pada pokoknya ditujukan bagi perlindungan hukum atas kepercayaan masyarakat terhadap kebenaran sesuatu. Verily, Allah is All-Hearing, All-Knowing. As long as the trial lasts until a court ruling with a fixed legal force, the Notaris act shall remain valid and bind the parties or any party to that act. According to the UNRWA, it was arranged that when Notaris in running his office was proven to have committed an infringement, then Notaris could be subject to or subject to sanctions, such as provisional sanctions, administrative and ethical codes of the Notaris office.